PENGARUH PERTUMBUHAN EKONOMI, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH TAHUN 2016-2019 - Sakti, Wahyu Bima; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Capital expenditures are budget expenditures for the acquisition of fixedassets and other assets that provide benefits for more than one accounting period.This study aims to analyze whether Economic Growth (PE), General AllocationFunds (DAU), and Special Allocation Funds (DAK) have a positive effect oncapital expenditure in districts / cities in Central Java. This study uses secondarydata in the form of PE data, DAK, DAU data from the Central Java ProvinceCentral Bureau of Statistics, and data from the ministry of finance. The sampleused in this study were 35 districts and cities in Central Java, sourced from theRegional Budget Realization Report (APBD) from 2016-2019. The data collectionmethod used in this research is purposive sampling method. The analytical toolused is multiple linear regression with t test, f test, and coefficient ofdetermination test.The results of this study indicate that economic growth (PE) has a positiveand insignificant effect on capital expenditure, while the General Allocation Fund(DAU) has a significant effect on capital expenditure and the Special AllocationFund (DAK) has a significant negative effect on capital expenditure.